2020
DOI: 10.1002/ffj.3628
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative analysis combining headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS) and intelligent (electronic) sensory systems to evaluate differences in the flavour of cultured pufferfish

Abstract: Pufferfish (Takifugu spp.) are rapidly becoming a valuable food commodity across Asia, making the flavour characterization of the different species economically significant. In this study, the flavour characteristics of four cultured pufferfish varieties (T obscurus, T flavidus, T bimaculatus and T rubripes) were evaluated using headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS) coupled with an electronic nose and electronic tongue. A total of 37 volatile compounds, primarily aldehydes and alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Therefore, PCA analysis was performed on the response value dataset of e-tongue ( Figure 9 B) to assess the effect of the increase in PP concentration and CA content on the taste of mackerel mince. The PC1 and PC2 accounted for 77.3% and 19.9% of the total variance, respectively, and the cumulative contribution of the first two PCs accounted for 97.2%, indicating that they were sufficient to explain the total variance in the dataset [ 49 ]. It could be observed that in the PCA analysis graph, it was easy to distinguish the samples with different concentrations and amounts of PP and CA; the products with 0.6% CA were located in the positive half-axis of y-axis, the products with 0.3% CA were located in the negative half-axis of x-axis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PCA analysis was performed on the response value dataset of e-tongue ( Figure 9 B) to assess the effect of the increase in PP concentration and CA content on the taste of mackerel mince. The PC1 and PC2 accounted for 77.3% and 19.9% of the total variance, respectively, and the cumulative contribution of the first two PCs accounted for 97.2%, indicating that they were sufficient to explain the total variance in the dataset [ 49 ]. It could be observed that in the PCA analysis graph, it was easy to distinguish the samples with different concentrations and amounts of PP and CA; the products with 0.6% CA were located in the positive half-axis of y-axis, the products with 0.3% CA were located in the negative half-axis of x-axis.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the PCA could represent most information of the samples. The PCA obtained by the dynamic PCA module has also been successfully applied in the discrimination analysis in studies of kiwifruits [ 21 ], oil [ 42 ], shrimp [ 43 ], and pufferfish [ 44 ], based on the volatile fingerprints obtained by GC-IMS. As shown in Figure 4 a, the sample A and C were at the right side.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the flavor aldehydes such as heptanal, octanal, and nonanal are products of the oxidation of oleic and linoleic acids [ 33 , 34 , 35 , 36 ]. At the end of the growing-out period, the volatile flavor compound profile was clearly different between the FO and PO groups.…”
Section: Discussionmentioning
confidence: 99%